ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. ORIENTAL PRIMASINERGI ENGINEERING PEKANBARU - Ozi Ahmad Sapitra; Dewita Suryati Ningsih; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the analysis influence of leadership style and organizational commitment partially or simultaneously on the job satisfaction employees at pt. oriental primasinergi engineering pekanbaru . The population in this study were all employees totaling 161 employees and 62 employees were sampled by using the formula slovin, using instrumental testing the validity, reliability and classic assumption test. The analytical method used in this study is descriptive analysis and multiple linear regression analysis using SPSS 22 for windows. From the results of the testing that has been done, simultane ous regression test (F-test) showed that the variables of orleadership style and organizational commitment simultaneously significant effecton job satisfaction employees. And the results of the partial test (t test) showed that the variables of leadership style and organizational commitment partially significant effect on job satisfaction employees. The result of the calculation of the coefficient of determination (R2) is equal to 0,453, which means, leadership style and organizational commitment affect the job satisfaction employees amounted to 45,3 %, while the remaining 54,7 % is influenced by other variables that no tex amined in this study.Keywords : Leadership Style, Organizational Commitmen, Job Satisfaction Employees.